Familiarity, Knowledge, Attitude and Willingness towards Genetic Counselling among the South Indian Population: 10.55131/jphd/2022/200217 - Revathy, K. Sofia; Praba, L. Jeya (Journal of Public Health and Development, 2022)
The effect of any kind of genetic disorder is almost irreversible in life, so it is very important to understand these disorders and the modern, effective preventive approaches available to reduce the familial and societal burden. This study aims to measure the awareness of Genetic Counselling (GC) and investigate personal factors like knowledge, attitude, and willingness towards the purpose of genetic counselling among the South Indian population. Individuals from the state of Tamil Nadu, Karnataka, Andhra Pradesh, Telangana, Kerala, and Pondicherry participated in the study. Knowledge score was generated for everyone, ranging from 19 to 42, with which varied results were generated compared to other variables. Four hundred and sixty-seven individuals completed the survey. About fifty-nine percent of the respondents reported familiarity with GC and the main source of knowledge was through media. Positive attitude and willingness towards GC were reported in the population. Knowledge of GC showed a different trend when compared to other studies of similar objectives. The need for more qualified professionals in the field and the inclusion of genetic counselling and testing as a primary preventive measure in government health care sectors will help reduce the burden of genetic diseases in families and society.